A bibliometric study of global trends in T1DM and intestinal flora research - Cui, Xinxin; Wu, Zhen; Zhou, Yangbo; Deng, Longji; Chen, Yu; Huang, Hanqiao; Sun, Xiangbin; Li, Yu; Wang, Haixia; Zhang, Li; He, Jia (Frontiers in Microbiology, 2024)
Background: Type 1 diabetes mellitus (T1DM) is a chronic metabolic disease that seriously jeopardizes human physical and mental health and reduces quality of life. Intestinal flora is one of the critical areas of exploration in T1DM research. Objective: This study aims to explore the research hotspot and development trend of T1DM and intestinal flora to provide research direction and ideas for researchers. Methods: We used the Web of Science (WOS) Core Collection and searched up to November 18, 2023, for articles on studies of the correlation between T1DM and intestinal flora. CiteSpace, VOSviewers and R package “bibliometrix” were used to conduct this bibliometric analysis. Results: Eventually, 534 documents met the requirements to be included, and as of November 18, 2023, there was an upward trend in the number of publications in the field, with a significant increase in the number of articles published after 2020. In summary, F SUSAN WONG (UK) was the author with the most publications (21), the USA was the country with the most publications (198), and the State University System of Florida (the United States) was the institution with the most publications (32). The keywords that appeared more frequently were T cells, fecal transplants, and short-chain fatty acids. The results of keywords with the most robust citation bursts suggest that Faecalibacterium prausnitzii and butyrate may become a focus of future research. Conclusion: In the future, intestinal flora will remain a research focus in T1DM. Future research can start from Faecalibacterium prausnitzii and combine T cells, fecal bacteria transplantation, and short-chain fatty acids to explore the mechanism by which intestinal flora affects blood glucose in patients with T1DM, which may provide new ideas for the prevention and treatment of T1DM.